Comparison of Several Indonesian Medicinal Plants Effects on LDL-C and IL-6 Levels in Wistar Rats After High Fat Feeding - Penny Setyawati Martioso; Diana Krisanti Jasaputra; Julia Windi Gunadi; Ronny Lesmana; Pinkan Al Shabrina (Faculty of Medicine, Universitas Padjadjaran, 2023)
High-fat diet habits lead to an increase in LDL-C levels that eventually influence the atherosclerotic plaque formation and progression, causing coronary heart disease. Atherosclerosis is a chronic inflammatory process that releases various pro-inflammatory cytokines, including IL-6. Indonesians often use medicinal plants to decrease cholesterol levels. This study aimed to compare the LDL-C and IL-6 levels after treatments of ethanol extracts from Java ginger (EEJG), turmeric (EET), garlic (EEG), and pomegranate flowers (EEPF) in a hypercholesterolemia animal model. This study was conducted at the Maranatha Biomedical Research Laboratory from June–December 2020. Male Wistar rats were divided into six groups (n=5 per group) and received high-fat feeding and 0.01% propylthiouracil. The following treatments were given for 28 days: oral carboxymethylcellulose 1% for negative control; 35 mg/200g of oral EEJG, EET, EEG, EEPF for respective treatment groups (n=5 groups); and 0.36 mg/200 g of oral Rosuvastatin for positive control. It was demonstrated that the mean LDL-C levels were 65.75 mg/dL, 55.25 mg/dL, 56.75 mg/dL, and 59.60 mg/dL for EEJG, EET, EEG, EEPF groups, respectively, which were significantly different from that of the negative control (81.73 mg/dL). The IL-6 levels of the EEJG (27.55 pg./mL) and EEG (27.54 pg./mL) group were significantly different from the EEPF group (24.5 pg./mL) but not significantly different from the negative control (25.58 pg./mL), EET (25.60 pg./mL), and rosuvastatin (26.09 pg./mL) groups. The administration of ethanol extracts of Java ginger, turmeric, garlic, and pomegranate flower decreases the C-LDL levels; however, only the ethanol extract of pomegranate flowers administered for 28 days decreases the IL-6 levels of Wistar rat hypercholesterolemia model, albeit insignificantly.